Fuzzy logic implementation and applications - Patyra, M.J. (Marek J.); Mlynek, D.M (Wiley Teubner, 1996)
Offering a new perspective on a growing field, the text explores the many hardware implications of fuzzy logic based circuits. As use of AI increases, so the VLSI area of circuits is becoming a growth subject. The text surveys fuzzy set theory before moving on to cover a range of nonstandard solutions for fuzzy logic VLSI circuits. An overview of future trends is included plus practical examples from the authors' research which will enhance the reader's understanding of the topic. This is the first book on hardware aspects of fuzzy systems which offers a mixture of classical work and the authors' new perspective.